Fine-Scale Mapping of Mega-Epibenthic Communities and Their Patch Characteristics on Two New Zealand Seamounts - Goode, Savannah L.; Rowden, Ashley A.; Bowden, David A.; Clark, Malcolm R.; Stephenson, Fabrice (Frontiers in Marine Science, 2021)
Seamounts are common features of the deep seafloor that are often associated with aggregations of mega-epibenthic fauna, including deep-sea corals and sponges. Globally, many seamounts also host abundant fish stocks, supporting commercial bottom trawl fisheries that impact non-target benthic species through damage and/or removal of these non-target species. However, the effects of bottom trawling on seamount benthic communities, as well as their recovery potential, will vary over the total seamount area because of differences in within seamount habitat and community structure. It is therefore important to understand fine-scale community dynamics, community patch characteristics, and the environmental drivers contributing to these patterns to improve habitat mapping efforts on seamounts and to determine the potential for benthic communities on seamounts to recover from fishing disturbances. Here we analysed the structure and distribution of mega-epibenthic communities on two New Zealand seamounts with different physical environments to determine which environmental variables best correlated with variation in community structure within each seamount. We used the identified environmental variables to predict the distribution of communities beyond the sampled areas, then described the spatial patterns and patch characteristics of the predicted community distributions. We found the environmental variables that best explained variations in community structure differed between the seamounts and at different spatial scales. These differences were reflected in the distribution models: communities on one seamount were predicted to form bands with depth, while on the other seamount communities varied mostly with broadscale aspect and the presence of small pinnacles. The number and size of community patches, inter-patch distances, and patch connectedness were found to differ both within and between seamounts. These types of analyses and results can be used to inform the spatial management of seamount ecosystems.